(3CSGSjGJ EOGQI GdhbJ ddhXjaI hGdMjGI GdYGeI (B/s - (3YdjGf, QHMj eUWais ((3YeGf(B: s (3OGQ LQjQ(B, s, 2011)
(3eaGgje CSGSjI aj GdhbJ h GOGQJg , YedjI GdJNWjW ddhbJ , eJWdHGJ GOGQI GdhbJ ,YedjI JfXje GdhbJ h JSLjdg , eVjYGJ GdhbJ , GSJZdGd GdhbJ h GOGQI eVjYGJg , GdJcfhdhLjG h GOGQI GdhbJ , OQGSGJ CQOfjI h YQHjI aj GOGQI GdhbJ , h GNjQG JhUjGJ YGeI dGOGQI GdhbJs
Keywords: (3EOGQI (B-(3GdhbJs; (3GdGOGQIs; (3GdhXjaI GdYehejIs